Twenty-Sixth Symposium on Biotechnology for Fuels and Chemicals
DOI: 10.1007/978-1-59259-991-2_89
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Steam Pretreatment of SO2-Impregnated Corn Stover for Fuel Ethanol Production

Abstract: In this study, corn stover with a dry matter content of 20% was impregnated with SO 2 and then steam pretreated for various times at various temperatures. The pretreatment was evaluated by enzymatic hydrolysis of the solid material and analysis of the sugar content in the liquid. The maximum overall yield of glucose, 89% of the theoretical based on the glucan in the raw material, was achieved when the corn stover was pretreated at 200°C for 10 min. The maximum overall yield of xylose, 78%, was obtained with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1
2

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 14 publications
2
23
1
2
Order By: Relevance
“…The xylose lost after a 30 min treatment might be caused by degradation of hemicellulose at 195°C. It has been reported that the degradation of xylose is much easier and faster than that of glucose [21][22][23][24]. Figure 2 shows the result of the sugar concentrations in the hydrolysates from the two-step pretreatment at four temperatures in the second pretreatment with hot water.…”
Section: Electrolyzed Water Pretreatmentmentioning
confidence: 99%
“…The xylose lost after a 30 min treatment might be caused by degradation of hemicellulose at 195°C. It has been reported that the degradation of xylose is much easier and faster than that of glucose [21][22][23][24]. Figure 2 shows the result of the sugar concentrations in the hydrolysates from the two-step pretreatment at four temperatures in the second pretreatment with hot water.…”
Section: Electrolyzed Water Pretreatmentmentioning
confidence: 99%
“…So far, methods such as ammonia fiber explosion (AFEX), wet oxidation and liquid hot water (LHW) treatment seem to be more successful for agricultural residues (11,65,66), whereas steam pretreatment has resulted in high sugar yields for both forestry and agricultural residues. Glucose yields >90% and xylose yields >80% were obtained after enzymatic hydrolysis, both with and without the addition of an acid catalyst (43,46,54,58).…”
Section: Pretreatmentmentioning
confidence: 98%
“…The pretreatments were performed at near optimal conditions that had previously been determined to provide maximum hemicellulose recovery while ensuring effective enzymatic hydrolysis of the cellulose component (steam pretreatment: corn stover [34], Douglas-fir [35], and poplar [36]). After pretreatment, the cellulose rich water insoluble components were washed, filtered and refrigerated for long-term storage.…”
Section: Lignocellulosic Feedstocks and Their Pretreatmentmentioning
confidence: 99%